-2(x + 3) = -2(x + 1) - 4
-2x - 6 = -2x - 2 - 4 <em>distributed -2 on the left and on the right</em>
-2x - 6 = -2x - 6
<u>+2x </u> <u>+2x </u>
-6 = -6
TRUE
Since this is a true statement, there are infinite solutions (aka All Real Numbers)
Answer: C
9514 1404 393
Answer:
(-5,1)
Step-by-step explanation:
To eliminate x, multiply the first equation by 3 and add 2 times the second equation.
3(-2x +7y) +2(3x -4y) = 3(17) +2(-19)
-6x +21y +6x -8y = 51 -38
13y = 13
y = 1 . . . . . matches the third answer choice
(x, y) = (-5, 1)
I love math and i believe tjat the answer to my belief is 2